2021
DOI: 10.1186/s12891-021-04424-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscle shear wave elastography, conventional B mode and power doppler ultrasonography in healthy adults and patients with autoimmune inflammatory myopathies: a pilot cross-sectional study

Abstract: Background Before the role of shear wave elastography (SWE) and B mode ultrasound (US) in the diagnosis of different forms of idiopathic inflammatory myopathies (IIM) can be investigated, normative data is required. This study aimed to describe and then compare normative SWE and B mode ultrasound metrics of muscles in healthy controls and patients with IIM. Methods Twenty nine healthy adult controls and 10 IIM patients (5 with inclusion body myosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…A total of 7 studies [ 25 , 36 , 37 , 38 , 39 , 40 , 41 ], with 108 IBM patients and 171 healthy controls, were included in the analysis. Four studies [ 25 , 36 , 38 , 41 ] reported the echogenicity of the flexor digitorum profundus (FDP) and gastrocnemius (GC) muscle groups with 168 participants (76 IBM patients and 92 controls).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 7 studies [ 25 , 36 , 37 , 38 , 39 , 40 , 41 ], with 108 IBM patients and 171 healthy controls, were included in the analysis. Four studies [ 25 , 36 , 38 , 41 ] reported the echogenicity of the flexor digitorum profundus (FDP) and gastrocnemius (GC) muscle groups with 168 participants (76 IBM patients and 92 controls).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [ 25 , 36 , 38 , 41 ] reported the echogenicity of the flexor digitorum profundus (FDP) and gastrocnemius (GC) muscle groups with 168 participants (76 IBM patients and 92 controls). Two studies [ 38 , 39 ] reported the muscle thickness of the FDP with 128 participants (46 IBM patients and 82 controls). Three studies [ 36 , 37 , 40 ] were involved in diagnostic test accuracy meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In group-level comparisons, muscle elasticity as determined by ultrasound SWE has been found to be altered in different myopathies [7,8,10], e.g., elasticity is likely reduced in idiopathic inflammatory myopathies (IIM) when compared to healthy controls [24,25]. Such features may serve as diagnostic indicators.…”
Section: Discussionmentioning
confidence: 99%